Evaluation Using Black Box Testing and System Usability Scale in the Kidung Sekar Madya Application - Mahendra, Gede Surya; Asmarajaya, I Kadek Andy (Politeknik Ganesha Medan, 2022)
Hearing about Bali is always synonymous with tourism, beautiful natural tourism potential, unique culture and friendly people and culture. The practice of Hindu religious ceremonies cannot be separated from elements of art and culture. The existence of Kidung Dharma Gita as Balinese culture among the younger generation has begun to fade. The implementation of the Yadnya ceremony in Bali, this song is sung by many parents and it is rare for young people to sing this kidung voluntarily. The purpose of this research is to carry out conservation for the sake of preserving the Kidung Dharma Gita culture, so it is necessary to digitize Balinese culture, especially in the Dharma Gita Sekar Madya song. One of the solutions offered is the creation of an Android-based application for Kidung Dharma Gita Sekar Madya. In the evaluation process using Black Box Testing and System Usability Scale (SUS). Black Box Testing tests the entire page display with 16 test cases that produce good and appropriate results for each test. SUS involved 58 respondents with 10 question instruments. The test results obtained a value of 75,560 in Raw SUS Scores, that can be stated that this application has a passive value in NPS, acceptable value in acceptability, good value in adjective, and reach grade B. It can be seen that this application is good and has uses in cultural preservation applications.